The Role of Interactive Learning Media in Deep Learning: A Study on Critical Thinking Skills in Elementary Schools - Sri Nur Rahmi; Wahidmurni Wahidmurni; Samsul Susilawati (International Journal of Educational Narratives, 2026)
Background: The development of twenty-first-century education requires students to possess higher-order thinking skills, particularly critical thinking, which enables them to analyze information, evaluate perspectives, and make reasoned decisions. In elementary education, the integration of interactive learning media and deep learning approaches is increasingly considered important to support meaningful learning and foster students’ cognitive development. Purpose: This study aims to analyze the role of interactive learning media in facilitating deep learning to support the development of critical thinking skills among elementary school students. Method: The study employed a mixed-method approach using a sequential explanatory design. Quantitative data were collected through a teacher perception questionnaire and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS software. Qualitative data were subsequently used to elaborate and interpret the quantitative findings. Results: The findings indicate that interactive learning media and deep learning have not yet demonstrated a strong direct effect on students’ critical thinking skills. However, both elements function as facilitators within the learning process. The development of critical thinking skills requires the consistent integration of analytical and reflective learning activities within classroom instruction. Conclusion: Interactive learning media and deep learning should be positioned as supporting components within the broader learning ecosystem rather than as standalone determinants of critical thinking development. Their effectiveness largely depends on how teachers integrate these elements with pedagogical strategies that encourage sustained student engagement, reflection, and meaningful learning experiences.